The Counseling Experiences of Individuals Who Are Estranged From a Family Member. Issue 4 (9th October 2019) - Blake, Lucy; Bland, Becca; Imrie, Susan
Abstract : Objective: For the first time, this study explored the counseling experiences of individuals estranged from a family member and the ways in which therapy was helpful, unhelpful, or both. Background: Family relationships are often assumed to be permanent. However, family members both can and do become estranged from one another, which can be a challenging experience, leading to feelings of sadness and loss and experiences or perceptions of stigma. Method: Findings are presented from an online survey of individuals who are estranged from one or more family members and had sought support from the charity Stand Alone. Open‐text responses were thematically analyzed from 209 respondents, 133 of whom elaborated on counseling experiences that had been helpful and 107 of whom described counseling experiences that had been unhelpful. Results: Helpful encounters with therapy were those in which respondents felt supported to make their own decisions about their family relationships, developed insight and understanding through working with professionals who were knowledgeable about estrangement, and moved forward in their lives. Conclusion: Therapy that is delivered by professionals who offer nondirective support (rather than suggesting that clients act or feel a certain way) and who are knowledgeable about estrangement will be of the greatest help and utility to individuals estranged from a family member. Implications: Commissioning bodies who offer support to estranged individuals need to ensure that counselors are knowledgeable about estrangement and that training on this issue is included in ongoing career professional development.